Edge cordial and total edge cordial labeling for eight sprocket graph - A. Sathakathulla, A.; G Fajlul Kareem, M. (International Journal of Applied Mathematical Research, 2021)
This papers deals with the Edge cordial labeling of newly introduced eight sprocket graph. This graph is already proven as cordial and gracious in graph labelling. In our study we have further proved that Eight Sprocket graph related families of connected edge-cordial graphs. Also the path union of Eight Sprocket graph, cycle of Eight Sprocket graph and star of Eight Sprocket graph are Edge-cordial.Â